2018
DOI: 10.1103/physrevb.97.140301
|View full text |Cite
|
Sign up to set email alerts
|

Quantum and classical ripples in graphene

Abstract: Thermal ripples of graphene are well understood at room temperature, but their quantum counterparts at low temperatures are in need of a realistic quantitative description. Here we present atomistic path-integral Monte Carlo simulations of freestanding graphene, which show upon cooling a striking classical-quantum evolution of height and angular fluctuations. The crossover takes place at ever-decreasing temperatures for ever-increasing wavelengths so that a completely quantum regime is never attained. Zero-tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…For physical membranes, the scaling exponent was calculated at leading and next-to-leading order, giving η 0.821 and η 0.789 respectively [18][19][20]. These results are compatible with predictions obtained by numerical simulations [13,19,[21][22][23][24][25][26][27][28][29]. Recently, the statistical mechanics of crystalline membranes has been revisited by non-perturbative renormalization group (NPRG) techniques [26,[30][31][32][33][34].…”
Section: Introductionsupporting
confidence: 77%
“…For physical membranes, the scaling exponent was calculated at leading and next-to-leading order, giving η 0.821 and η 0.789 respectively [18][19][20]. These results are compatible with predictions obtained by numerical simulations [13,19,[21][22][23][24][25][26][27][28][29]. Recently, the statistical mechanics of crystalline membranes has been revisited by non-perturbative renormalization group (NPRG) techniques [26,[30][31][32][33][34].…”
Section: Introductionsupporting
confidence: 77%
“…We would like to reinforce that even neglecting out-of-plane vibrational modes, our results for the flat membrane are a good reference for first estimates because they resemble the physics of a free-standing graphene monolayer in agreement with experiments. Very recently, PIMC simulation results [48] in agreement with [49] have shown that the crossover between classical and quantum contribution for the out-of-plane vibrational modes should occur around 50K. For lower temperatures quantum fluctuations should leave the membrane flat on the large scale.…”
Section: Numerical Results and Discussionsupporting
confidence: 52%
“…In contrast to our MD results for σ 0 , previous Monte Carlo (MC) works claim that such term should not be present. 20,52 Both MD and MC methods should provide identical results. The origin of this disagreement is not clear, but it might be due to inaccuracies in the sampling of the sluggish long-wavelength modes.…”
Section: Surface Tensionmentioning
confidence: 99%